Aborsi dalam Perspektif Hak Asasi Manusia dan Hukum Islam (Analisis terhadap Peraturan Pemerintah No. 61 tahun 2014 tentang Kesehatan Reproduksi) - Fidawaty, Linda (Universitas Islam Negeri Raden Intan Lampung, 2017)
This article examines the Government Regulation PP No. 61 of 2014 regulating mechanism and procedures of abortion in the case of rape victims from the perspectives of Human Rights and Islamic Law. The regulation, which is the implementation of Article 75 paragraph (1) of the Health Act, states that abortion is prohibited unless there is an indication of medical emergency and pregnancy due to rape. According to the rules, the implementation of abortion must fulfill some procedures such as:pregnancy verification, doctor’s certificate, investigator’s statement, and psychologist’s information about the occurrence of rape. In 39/1999 ofHuman Rights Act, unless it is aimed atprotecting the mother and child’s life, abortionis considered as violating human rights. In Islamic law, the regulation of abortion for rape victims varies widely, depending on circumstances.